Suffix Variations in Verbal Constructions of Dialects in Oyi Local Government Area, Anambra State - Amaka Yvonne Okafor; Muhammad Ridwan (LingLit Journal Scientific Journal for Linguistics and Literature, 2024)
This study investigates the linguistic landscape of Oyi Local Government Area in Anambra State, Nigeria, focusing on suffix variations in verbal constructions across its diverse dialects. The research documents and analyzes how suffixes are used in past tense, future tense, perfective aspect, and negation constructions in the dialects spoken in Awkuzu, Nteje, Ogbunike, Nkwelle Ezunaka, and Umunya. A descriptive and comparative linguistic approach was employed, involving fieldwork and structured interviews with native speakers from these towns. The data collected were transcribed and analyzed using phonological and morphological frameworks to identify patterns and variations. Through a detailed analysis, it was found that past tense constructions generally featured a common prefix and root verb across most towns, with Umunya notably employing a distinct suffix pattern. Future tense constructions relied heavily on auxiliary verbs, with towns like Awkuzu and Ogbunike using ‘ga-’ while Nkwelle Ezunaka utilized ‘na-’. In perfective constructions, a consistent suffix was observed, but root verbs and immediate suffixes varied slightly, as seen with Nkwelle Ezunaka’s use of ‘je-ve’ compared to others using ‘je-be’. Negation constructions revealed the most diversity, with Awkuzu and Nteje using the standard suffix ‘-ghi’, while Umunya, Ogbunike, and Nkwelle Ezunaka employed distinct negation markers like ‘-ra’, ‘-rϙ’, and ‘-zi’, respectively. These findings highlight the rich linguistic diversity within the region and underscore the importance of documenting and preserving these dialectal variations.